MAJEED AMJAD’S PERSPECTIVE OF UNIVERSE AND METAPHYSICAL APPROACH - Dr. Nabeel Ahmad Nabeel; Dr. Sher Ali (Zaban-o-Adab, 2022)
Majeed Amjad is one of the stalwarts of modern, post - independence Urdu poetry. In his poetry we can find at one and the same page discussion of matters deeply philosophical and central to human existence, and at the same time we find reflections of ordinary people and their seemingly ordinary lives in an idiom that matches their particular locale. We find such a reflection in Amjad's poem ' The Well '. In this poem we find both the above-mentioned characteristics of Amjad's poetry. In the poem an ordinary village well and its working have been taken away from their immediate context and given a new, profounder meanings. The well is a metaphor for universal system, a metaphysical construct which is oblivious to ordinary humans and consequences that they have to face in the course of movement and working of universe. The poem ' The Well ' is not only a sequence of ordinary life events, but at a deeper level reflects an acute understanding on the part of the poet, mechanism of how the universe works and how indifferent it's controlling power is to fate of ordinary mortals. In this article these issues have been discussed at length.